(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Prostatic stromal sarcoma is an extremely rare malignant tumor arising from the mesenchymal stromal component of the prostate. Its nonspecific clinical presentation and the typically non-elevated serum PSA level make the preoperative diagnosis particularly challenging. Case Presentation: We report the case of a 42-year-old man who was admitted with progressive urinary retention. He had no fever or pelvic pain, and his serum PSA level was within the normal range. Pelvic magnetic resonance imaging (MRI) demonstrated a large mass predominantly involving the right side of the prostate and occupying nearly the entire gland. The lesion contained hemorrhagic cystic components and heterogeneously enhancing solid portions after gadolinium administration. The patient underwent radical prostatectomy, and the diagnosis of prostatic stromal sarcoma was established postoperatively. Conclusion: Prostatic stromal sarcoma is a rare entity that should be considered in the differential diagnosis of a large mixed solid-cystic prostatic mass, particularly in relatively young patients without elevated serum PSA levels. MRI plays an important role in characterizing the lesion, assessing local extent, and suggesting the diagnosis preoperatively.